2011
DOI: 10.1007/s00268-011-1128-1
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Experience in the Treatment of Spontaneous Aorto‐venous Fistulas in a Developing Country

Abstract: Spontaneous AVFs caused by aneurysmal rupture are not uncommon, and they require prompt surgical or endovascular treatment. Routine use of multislice CT in patients with acute aortic syndrome is probably the best way to the correct diagnosis of aorto-venous fistulas and planning of the optimal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…However, we performed a contrast-enhanced CT to make the details of anatomy of the ruptured aneurysm and the other intraoperative bleeding from the fistula. 5,8,9) In this case, preparation was made to insert an occlusion catheter through the femoral vein. However, it was not used because bleeding was successfully controlled manually.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we performed a contrast-enhanced CT to make the details of anatomy of the ruptured aneurysm and the other intraoperative bleeding from the fistula. 5,8,9) In this case, preparation was made to insert an occlusion catheter through the femoral vein. However, it was not used because bleeding was successfully controlled manually.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,9) There have been multiple recent reports on endovascular stent-grafts to treat aorto-caval fistulas caused by abdominal aortic aneurysms. 5,10) Endovascular treatment is an attractive modality because it is minimally invasive and causes less blood loss than open surgery. In this case, we thought that endovascular treatment could be difficult because of the fistula was located in the left renal vein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the dawn of the endovascular age, most ACF had been repaired primarily in an open fashion and the literature accounted the surgical mortality to be as high as 16–66%. 4,5 However, after Beveridge et al 6 in 1998 reported the first endovascular repair of ACF, many have published reports of ACF describe endovascular management. We sought to review the contemporary outcomes and complications of both methods, present a successful case of open repair, and determine if endovascular repair was associated with improved outcomes.…”
Section: Introductionmentioning
confidence: 99%